PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TTW (THINK TALK WRITE) TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI PESERTA DIDIK KELAS V DI SEKOLAH DASAR - Dita Khaerunnisa; Dindin M.Z.M; Feby Inggriyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research was motivated by problems found in class V at SDN Budhi Karya, namely the lack of students' ability to write narrative essays. The type of research used by researchers is a quantitative approach with quasi-experimental or experimental research like an experiment focuses on designnonequivalent control group design. The population used by researchers is all class V students at SDN Budhi Karya, and the sample used by researchers is class VA which is the experimental class and class VB is the control class. The sample in this study used techniques sampling purposive. The instruments used in data collection were tests, namely pretests and posttests to measure students' essay writing skills after being given treatment. The results of the research show that the use of the think talk write type cooperative learning model has an influence with an effect size value of 0.37 in the medium category.